Perceptions and Opinions towards Cell Phone Use as a Risk Factor of Brain Cancer among University Students in Malaysia - Al-Naggar, Redhwan Ahmed; Bobryshev, Yuri V (Asian Journal of Medical Sciences, 2013)
The worldwide use of cell phones has rapidly increased over the past decades. With the increasing use of mobile phones, concern has been raised about the possible carcinogenic effects as a result of exposure to radiofrequency electromagnetic fields. The objective of this study was to explore the perceptions and opinions towards brain cancer related to cell phone use among university students in Malaysia. The study revealed that the majority of the study participants believe that there is no relationship between brain cancer and hand phone use. DOI: http://dx.doi.org/10.3126/ajms.v4i1.7808 Asian Journal of Medical Sciences 4(2013) 1-4